Syntactic variation in Insular Scandinavian - Höskuldur Þráinsson, 1946-; Heycock, Caroline B., 1960-; Petersen, Hjalmar P.; Hansen, Zakaris Svabo (Studies in Germanic linguistics, 2017)
This book presents the latest research on the syntax of the "Insular Scandinavian" languages (Faroese and Icelandic), with contributions from thirteen experts, and a significant introductory chapter by the four editors. The topics covered include some that have figured extensively in recent literature on Scandinavian syntax and its implications for syntactic theory: case, agreement, embedded clause word order, stylistic fronting, and the nature of "expletive" constructions. The volume is conceived around the topic of variation, both within and between the two languages studied-as well as more generally-and stands out for the wealth of new empirical detail from both Faroese and Icelandic, relating to each of the topics and theoretical issues discussed. Each chapter is written in a way to make it accessible to a wide audience within linguistics; the book will be essential reading for students and researchers with an interest in the syntax of the Germanic languages.